Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan di Hotel Rangkayo Basa Kota Padang - jihan nur fahira; Youmil Abrian; Nidia Wulansari (Departemen Pariwisata Universitas Negeri Padang, 2022)
This research is motivated by employee dissatisfaction which is influenced by a high workload and an unfavorable work environment. The type of research used is quantitative with a causal approach. Respondents in this study used a total sampling technique which consisted of 36 employees of the Rangkayo Basa Padang Hotel. The type of data from this research is the type of primary data. This research instrument uses a questionnaire (questionnaire) that has been compiled according to a Likert scale that has been tested for validity and reliability first. Hypothesis testing using multiple regression analysis. Based on the results of hypothesis testing, the Adjusted R Square number is 0.613, in other words, the effect of workload and work environment variables on employee job satisfaction is 61.3% and 38.7% is determined by other factors. Furthermore, the calculated F is 28,742 with sig. 0.000 <0.05, it can be concluded that the workload variable (X1) and the work environment variable (X2) have a significant effect on the employee job satisfaction variable (Y). So it can be concluded that the research hypothesis is Ha is accepted and H0 is rejected. The t-value of the workload variable is -2.154 with a significance of 0.039 <0.05 and the t-value of the work environment variable is 5.378 with a significance of 0.000 <0.05. This means that every increase of 1 unit of workload (X1) will reduce the level of job satisfaction (Y) by 2,154 and it means that there is a unidirectional effect between work environment and job satisfaction, where every increase of 1 unit of the work environment (X2) will increase job satisfaction (Y). 5,378.